O. O. Potebnja’s scholar formation in the light of the discussion with P. O. Lavrovskij - Радзієвська, Тетяна Вадимівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2021)
The paper deals with the situation which emerged after the publication of O. O. Potebnja’s (A. A. Potebnya’s) work „On mythical significance of the rituals and the superstitions” (1865) where some problems of comparative  mythological studies were examined. This work became an object of critical analysis accomplished by professor of  Kharkov  university P. O. Lavrovskij, Potebnja’s  teacher, who wrote and published (1866) a voluminous critical review text (102 pages) in the genre of razbor  „an analytical book review” which represented the reviewing traditions of the academic discourse in XIX c. O. O. Potebnja’s text which contains the replies to the critique of his teacher in the razbor remains as a whole still unpublished and is preserved as an archive document. In Potebnja studies it is conventionally named „The reply”. So the textual base for the analysis of this discussion includes three texts, two last of which are under consideration in the paper.The text of P. O. Lavrovskij’s  razbor is notable for its extremely detailed analysis of Potebnja’s work with the use of rare sources, extra information from manuscripts, vocabularies, academic works on mythology, history and culture of different peoples, on linguistics and comparative studies. The text shows that P. O. Lavrovskij’s  attention is directed mainly to the methodological aspect of Potebnja’s research: his critical remarks cover almost all methods of analysis, especially, the procedures dealing with establishment of identity or similarity of the mythical objects. Discussing with P. O. Lavrovskij O. O. Potebnja demonstrates an equal status to his opponent, his vast commentaries in the text of „The reply” correspond to the deep understanding of the nature of mythical space. His position in this textual discussion is marked by maturity of considerations and highly informative answers to his opponent.The author comes to the conclusion that the discussion represents the situation of methodological conflict, typical for the history of Slavic studies in XIX c., which nevertheless creates stimuli for elaborating methodological foundations in philological science.